Sustainable Lighting Layout in Urban Areas: Maximizing Implicit Coverage and Minimizing Installation Cost - Hammad, Ahmed W. A.; Akbarnezhad, Ali (Frontiers in Built Environment, 2018)
A key decision in the design of urban lighting is the location of the luminaries that are used to illuminate the specified region. The decision needs to account for coverage requirements identified in certain areas, based on safety considerations and nature of work activity, along with ensuring the cost effectiveness of the installation pattern adopted. In this work, a novel approach is presented via a multi-objective mathematical optimisation model that results in a sustainable layout of light poles in urban region. A maximal coverage objective, with implicit demand cover, is formulated as a measure of the social requirement in urban lighting, which models security and safety associated with night-time lighting of the urban region. At the same time, the economical aspect of the layout is considered via minimising the installation cost of the lighting layout. A realistic case example is then solved using the ϵ-constraint method. A Pareto optimal front for the case considered is constructed and analysed.